PTU-066 The gut microbiota influences intestinal epithelial proliferative potential. (8th June 2018) - Thomas, John P; Parker, Aimee; Divekar, Devina; Pin, Carmen; Watson, Alastair
Abstract : Introduction: The intestinal epithelium is comprised of a single layer of cells which serves a number of critical functions including the formation of a physical barrier to environmental pathogens and chemical substances, and the absorption of essential nutrients, electrolytes and water. It is also the site of the gut microbiota, a complex and diverse community of bacteria, viruses and fungi, which exists in a mutually beneficial relationship with the human host. The epithelial barrier is maintained through tightly regulated processes of stem cell renewal, epithelial maturation, cell migration and cell death. Failure to finely coordinate these processes can lead to disease states such as cancer. In this study, we aimed to investigate and characterise the role of the intestinal microbiota on epithelial cell proliferation. Methods: We determined the rates of epithelial proliferation in the intestines of Specific-Pathogen-Free (SPF) mice and Germ-Free (GF) mice. We utilised a previously described method which integrates cell tracking using the thymidine analogue Bromodeoxyuridine (BrdU) in crypt-villus units, with a tailored mathematical model, to assess the spatiotemporal dynamics of epithelial cell behaviour in SPF and GF conditions. Results: The rate of epithelial cell production in GF conditions was significantly slower in the colon, ileum and jejunum in comparison to SPF conditions. In the duodenum, there were no significant differences in proliferation rates in GF and SPF conditions. Cell production rates progressively decreased towards the distal part of the intestine, which inversely correlate with the concentration of organisms constituting the intestinal microbiota. Conclusions: These findings indicate that the gut microbiota plays an important role in determining intestinal epithelial cell proliferation rates. This relationship may have important implications in conditions such as colorectal cancer and inflammatory bowel disease, where differences in microbial signatures are known to exist. In turn, it may be possible to harness this knowledge to alter disease progression by modifying the host microbiota.